A Testing Framework for Joint Communication and Sensing in Synthetic Aperture Radars - Alex Piccioni; Roberto Alesii; Fortunato Santucci; Fabio Graziosi (IEEE Access)
Nowadays the modern progress in wireless communication technologies is motivating the mutual integration of heterogeneous services, in particular enabling resource and hardware-saving in platform deployment. In this perspective, Integrated Sensing and Communications (ISAC) is emerging as one of the most promising areas of research, especially for sensing technologies that are not originally designed for communication purposes, such as radar and Synthetic Aperture Radar (SAR). Current approaches leverage code modulation techniques through specific ground targets, which enable communication integration within SARs without requiring hardware modification. Besides, code transparency reduces the contribution of the target with low additive interference into the final SAR images. However, ISAC testing in real SAR systems poses numerous challenges. This paper introduces a novel testing framework that enables comprehensive evaluation of ISAC functionalities without the operational constraints of real-time tests. The framework provides flexibility across SAR platforms, operational parameters, and acquisition modes, ensuring practical, scalable, and cost-effective validation of communication embedding in SAR systems. To validate the proposed testing framework, real raw data from the ESA Sentinel-1 constellation have been employed to emulate ISAC target behaviour, demonstrating the effectiveness of the framework.